Analysis of the Effect of Quay Container Crane Available on Dwelling Time at Jakarta International Container Terminal - Gurning, Ridho Hans; Dendra, Feby Gusti; Shalihah, Adinda Rahmah (Politeknik STMI Jakarta, 2024)
The efficiency of loading and unloading dwelling time at the port has been done a lot. The problem at PT JICT is that there has been a decrease in throughput for the last three years, this has an effect on operational performance. operational performance is a representation of the achievement of all targets, thus the company always aims to improve its operational performance. Another problem is that the terminal's operational equipment has begun to be obsolete, which hinders the loading and unloading operation time, the lack of operational equipment that supports the loading and unloading process. The operational equipment studied is the Quay Container Crane which is seen from the available condition. All of these problems will have an impact on dwelling time at PT JICT which can affect operational performance. This research is expected to provide recommendations to PT Jakarta International Container Terminal to prepare adequate operational equipment so that the resulting dwelling time is known. This research method uses a dynamic system model and validation test with behavior pattern test. The results of the dynamic system model validation obtained dwelling time between 2.79 - 4.56 days, mean error of 3% and standard deviation error of 11%. Maintenance of quay container cranes has an influence on unloading productivity which has an impact on dwelling time. Based on 60 data, the quay container crane available variable is seen based on quartile values consisting of quartile 1 (Q1), quartile 2 (Q2) and quartile 3 (Q3). In the quay container crane available variable, the dwelling time value in quartile one is 1.34 days, quartile two is 1.47 and quartile three is 1.51 and the dwelling time value in quartile one is 14 units, quartile two is 12 units and quartile three is 10 units.